2013
DOI: 10.1158/1541-7786.mcr-13-0330-t
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B10, a Transcriptional Target of p53, Is Downregulated in Colorectal Cancers Associated with Poor Prognosis

Abstract: p53 is one of the most important tumor suppressor genes, and it is frequently inactivated in various cancers. p53 modulates various cellular functions, such as apoptosis and cell-cycle arrest via transcriptional regulation. Recently, p53 has been reported to be involved in a wide range of cellular metabolic pathways, including glycolysis, oxidative phosphorylation, glutaminolysis, and the antioxidant response. To understand the functional mechanism of p53, it is important to find out the direct transcriptional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…The expression of AKR1B10 is known to be increased in many human cancers including breast cancer and lung cancer (48, 49), but is diminished in colorectal cancer (50). We found that AKR1B10 expression is also diminished in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of AKR1B10 is known to be increased in many human cancers including breast cancer and lung cancer (48, 49), but is diminished in colorectal cancer (50). We found that AKR1B10 expression is also diminished in ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1B10 may exert disparate functions in tumorigenesis dependent upon the cellular context. Furthermore, it has been considered as a valuable prognostic marker for certain cancers . However, there have been no previous reports on AKR1B10 protein expression in OSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Ohashi Abbreviations: AKR, aldo-keto reductase; TPA, 12-O-tetradecanoyl phorbol 13-acetate; PKC, protein kinase C; cPKC, conventional PKC; nPKC, novel PKC; aPKC, atypical PKC; ERK, extracellular signal regulate kinase; SPAK/JNK, stress-activated kinase/c-Jun N-terminal kinase. 78 inhibited tumor proliferation [12]. The expression of AKR1B10 was 79 significantly lower in gastric cancer than in paired, normal mucosa 80 [13].…”
mentioning
confidence: 96%